2008
DOI: 10.1007/s00284-008-9121-0
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose-Producing Enzymes MTSase and MTHase in Anabaena 7120 Under NaCl Stress

Abstract: Salt tolerance, a multigenic trait, necessitates knowledge about biosynthesis and function of candidate gene(s) at the cellular level. Among the osmolytes, trehalose biosynthesis in cyanobacteria facing NaCl stress is little understood. Anabaena 7120 filaments exposed to 150 mM: NaCl fragmented and recovered on transfer to -NaCl medium with the increased heterocysts frequency (7%) over the control (4%). Cells failed to retain Na+ beyond a threshold [2.19 mM/cm3 (PCV)]. Whereas NaCl-stressed cells exhibited a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Today they are nearly ubiquitous in distribution and are found in extremes of environments ranging from hot springs [192][193][194] 2 Osmoticum [195][196][197] 3 Desiccation [47,198,103,199,87] 4 Gamma radiation [108,116,87,141,200,142] 5 Nutrition deficiency [201][202][203] 6 Heat [204,205] 7 Cold [206] 8 UV [191,207] 9…”
mentioning
confidence: 99%
“…Today they are nearly ubiquitous in distribution and are found in extremes of environments ranging from hot springs [192][193][194] 2 Osmoticum [195][196][197] 3 Desiccation [47,198,103,199,87] 4 Gamma radiation [108,116,87,141,200,142] 5 Nutrition deficiency [201][202][203] 6 Heat [204,205] 7 Cold [206] 8 UV [191,207] 9…”
mentioning
confidence: 99%
“…Increase in the sugar content observed could therefore, be related to the survival of the organisms at higher concentrations of salt. (Asthana et al, 2008) observed enhanced trehalose content in the cyanobacterium Anabaena 7120 under salinity stress.…”
Section: Resultsmentioning
confidence: 85%
“…Increase in the sugar content observed could therefore, be related to the survival of the organisms at higher concentrations of salt. Asthana et al (2008) observed enhanced trehalose content in the cyanobacterium Anabaena 7,120 under salinity stress. The variation observed amongst the strains with respect to the cellular constituents could be attributed to differences in the physiological status of the organisms.…”
mentioning
confidence: 85%